Ijtihad and its relationship with maslahah : An analysis review - Mansor, Sulaiman; Muhammad Azizur Rahman, Ramli; Hasan, Ahmad (Universiti Malaysia Pahang, 2019)
This paper aims to study the relationship between ijtihad and maslahah. The selection of maslahah compared to other arguments that play a role in the process of ijtihad is because it is an argument that is required to answer new questions that cannot be answered primarily through ijtihad within the scriptures range (ijtihad Bayani and ijtihad analogous). Without denying the ijtihad within the scriptures range, understanding of the maslahah itself is required. Despite that, this article explains its relationship only and subsequently presents a few examples of applications of maslahah in ijtihad as an exposure toward the reasonability of the usage in dealing with new issues today. Finally, it is expected that this article can be a guidance in determining the law to new arguments that have no direct explanation from the verses of al-Quran and al-Hadith.